2020
DOI: 10.2147/cia.s243233
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Tilburg Frailty Indicator (TFI): New Evidence for Its Validity</p>

Abstract: Objective: The Tilburg Frailty Indicator (TFI) is a self-report user-friendly questionnaire for assessing multidimensional frailty among community-dwelling older people. The main aim of this study is to re-evaluate the validity of the TFI, both cross-sectionally and longitudinally, focusing on the predictive value of the total TFI and its physical, psychological, and social domains for adverse outcomes disability, indicators of healthcare utilization, and falls. Methods: The validity of the TFI was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 42 publications
6
63
0
1
Order By: Relevance
“…The TFI, however, clearly has a poor association with visits to a general practitioner 1,9,42 and hospitalization. 1,13,[37][38][39]42,43 In all six studies using quality of life as the outcome, the TFI showed good associations with lower quality of life, independent of the quality of life instrument that has been used. 1,10,[40][41][42]45 Moreover, the TFI predicted mortality, with only Op Het Veld et al 43 qualifying the predicted value for this outcome as low.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The TFI, however, clearly has a poor association with visits to a general practitioner 1,9,42 and hospitalization. 1,13,[37][38][39]42,43 In all six studies using quality of life as the outcome, the TFI showed good associations with lower quality of life, independent of the quality of life instrument that has been used. 1,10,[40][41][42]45 Moreover, the TFI predicted mortality, with only Op Het Veld et al 43 qualifying the predicted value for this outcome as low.…”
Section: Discussionmentioning
confidence: 94%
“…In many studies focusing on criterion validity (concurrent and predictive), adverse outcomes of interest were disability, increased health-care utilization, lower quality of life and mortality. Regarding disability, studies predominantly show results that are excellent, 1 , 9 , 38 , 42 , 47 with AUCs >0.80. 29 The findings pertaining to an increase in health-care utilization present a less unambiguous picture and seem to depend strongly on the indicator used (eg, personal care, informal care, visits to a general practitioner or hospitalization).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations